2014
DOI: 10.1182/blood-2014-01-547927
|View full text |Cite
|
Sign up to set email alerts
|

Shear enhances thrombopoiesis and formation of microparticles that induce megakaryocytic differentiation of stem cells

Abstract: • Physiological shear stress promotes megakaryocytic maturation, DNA synthesis, phosphatidylserine exposure and caspase-3 activation.• Shear enhances the production and function of PLPs and Mk-derived microparticles possessing a novel function.In vivo visualization of thrombopoiesis suggests an important role for shear flow in platelet biogenesis. In vitro, shear stress was shown to accelerate proplatelet formation from mature megakaryocytes (Mks). Yet, the role of biomechanical forces on Mk biology and platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
137
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 60 publications
(73 reference statements)
6
137
1
Order By: Relevance
“…In circulation, MKs might experience different levels of biomechanical forces. Notably, MKs may experience higher levels of shear and for longer periods of time in the lung vasculature as detailed in our 2014 article (8). It has been shown that shear stress promotes MK morphological maturation, increased DNA synthesis, and extensive plateletlike particle (PLP), PPT, and MK-microparticle production (7,8).…”
Section: Megakaryocytes (Mks)mentioning
confidence: 93%
See 4 more Smart Citations
“…In circulation, MKs might experience different levels of biomechanical forces. Notably, MKs may experience higher levels of shear and for longer periods of time in the lung vasculature as detailed in our 2014 article (8). It has been shown that shear stress promotes MK morphological maturation, increased DNA synthesis, and extensive plateletlike particle (PLP), PPT, and MK-microparticle production (7,8).…”
Section: Megakaryocytes (Mks)mentioning
confidence: 93%
“…Mature MKs may squeeze through the incomplete endothelial lining of bone marrow capillaries to shed pro/preplatelets (PPT) into circulation under shear forces generated by the blood flow (6 -8). Less mature MKs may enter circulation and mature and shed PPT in the lung vasculature, thus being exposed to a wide spectrum of shear and other biomechanical forces (8). The evidence for the physiological importance of shear forces in platelet biogenesis has been established based on a series of studies and notably in Refs.…”
Section: Megakaryocytes (Mks)mentioning
confidence: 99%
See 3 more Smart Citations